Quantitative Determination of p-Cymene, Thymol, Neryl Acetate, and β-Caryophyllene in Different Growth Periods and Parts of Eupatorium fortunei Turcz. by GC-MS/MS. (2nd August 2021) - Nan, Guanjun; Zhang, Lina; Liu, Zhengzheng; Liu, Yu; Du, Yan; Zhao, Hongwen; Zheng, Hongxia; Lin, Rong; Yang, Guangde; Zheng, Shaohua
Abstract : Eupatorium fortunei Turcz. is a widely used Chinese herbal medicine in China. In this study, a gas chromatography-triple quadrupole mass spectrometry (GC-MS/MS) method was developed and validated to simultaneously determine the contents of p -cymene, thymol, neryl acetate, and β -caryophyllene in roots, stems, and leaves of Eupatorium fortunei Turcz. harvested at different growth periods. All four constituents could be detected in leaves, three could be detected in stems except β -caryophyllene, and only thymol could be detected in roots. The order of the total contents of four constituents in different parts was leaves > stems > roots. It indicated that the leaves could be the proper medicinal parts of Eupatorium fortunei Turcz. The content of four constituents in leaves varied a lot among different growth periods and showed an M-shaped change trend with the growth of Eupatorium fortunei Turcz. The four constituents accumulated to the highest values in early July followed by mid-September. Accordingly, the best harvest time of Eupatorium fortunei Turcz. is early July and mid-September.